THE POLITICAL ECONOMY BEHIND ENERGY SUBSIDY POLICY: IMPLICATIONS FOR INFLATION IN INDONESIA - Hendri Bin Muhammad Nur (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
Energy subsidy policy remains a central component of Indonesia’s economic governance due to its significant implications for inflation, fiscal sustainability, and social welfare. While previous studies have predominantly examined either the economic consequences of energy subsidies or the political challenges associated with subsidy reform, limited attention has been given to the interaction between these dimensions within a comprehensive political economy framework. This study aims to analyze how energy subsidy policies influence inflation in Indonesia and to examine the political, fiscal, and social factors that shape subsidy-related decision-making. Employing a qualitative research design, the study utilizes document analysis of government reports, budget documents, publications from Statistics Indonesia (BPS), reports from international organizations, and relevant academic literature. The data were analyzed using thematic content analysis to identify patterns linking energy subsidies, inflation dynamics, fiscal conditions, and political incentives. The findings indicate that energy subsidies contribute to short-term price stability by reducing energy-related production and transportation costs, thereby moderating inflationary pressures. However, prolonged reliance on subsidies generates fiscal burdens, distorts market incentives, and increases vulnerability to external energy price shocks. The analysis further reveals that subsidy policies are strongly influenced by political considerations, including electoral incentives, public expectations, and concerns regarding social stability, which often constrain reform efforts. Although subsidy reforms tend to trigger short-term inflationary effects, they can enhance fiscal sustainability, improve resource allocation efficiency, and support long-term economic resilience when accompanied by appropriate social protection measures. This study contributes to the literature by offering an integrated political economy perspective that connects economic, political, social, and environmental dimensions of energy subsidy policy. The findings suggest that sustainable inflation management requires a balanced policy framework that combines fiscal discipline, targeted social assistance, and long-term energy transition strategies to promote both macroeconomic stability and inclusive development.